2010
DOI: 10.1007/s13238-010-0144-5
|View full text |Cite
|
Sign up to set email alerts
|

High affinity soluble ILT2 receptor: a potent inhibitor of CD8+ T cell activation

Abstract: Using directed mutagenesis and phage display on a soluble fragment of the human immunoglobulin superfamily receptor ILT2 (synonyms: LIR1, MIR7, CD85j), we have selected a range of mutants with binding affinities enhanced by up to 168,000-fold towards the conserved region of major histocompatibility complex (MHC) class I molecules. Produced in a dimeric form, either by chemical cross-linking with bivalent polyethylene glycol (PEG) derivatives or as a genetic fusion with human IgG Fc-fragment, the mutants exhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…As LAG-3 binding to pHLA-II molecules has been shown to block consequent CD4 binding at the cell surface [19], competition between LAG-3 and CD4 for pHLA-II binding would favor engagement by LAG-3, potentially contributing to LAG-3 mediated T cell inhibition. It is noteworthy that the LAG-3 affinity for pHLA-II reported here (K D = 6.9-13.1 μM) is similar to that of the pHLA-I co-inhibitory receptor, ILT2 (K D = 7 μM) [26], which interferes with pHLA-I restricted T cell function [39]. We also demonstrated that pHLA-DR1 multimers weakly stain LAG-3 + cells.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…As LAG-3 binding to pHLA-II molecules has been shown to block consequent CD4 binding at the cell surface [19], competition between LAG-3 and CD4 for pHLA-II binding would favor engagement by LAG-3, potentially contributing to LAG-3 mediated T cell inhibition. It is noteworthy that the LAG-3 affinity for pHLA-II reported here (K D = 6.9-13.1 μM) is similar to that of the pHLA-I co-inhibitory receptor, ILT2 (K D = 7 μM) [26], which interferes with pHLA-I restricted T cell function [39]. We also demonstrated that pHLA-DR1 multimers weakly stain LAG-3 + cells.…”
Section: Discussionsupporting
confidence: 73%
“…Although informative, it is difficult to rule out the contributions of other molecules at the cell surface in shaping these interactions [20,21]. Further experimental evidence, showing that LAG-3 can block the pHLA-II-CD4 interaction, suggested that LAG-3 might bind to pHLA-II at a similar site to CD4 [22,23], analogous to the characteristics of Ig-like transcript 2 (ILT2) and CD8 that compete for binding to pHLA-I [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Our data suggest that autoreactive CD8 + T-cells can be preferentially targeted using blocking anti-CD8 antibodies. Additional modalities could also be employed based on the underlying biology, such as rationally designed small molecular inhibitors and soluble versions of the inhibitory immunoglobulin-like transcript 2 (ILT2) receptor 58 . These approaches hold the potential to suppress pathogenic CD8 + T-cell-mediated autoimmunity without the attendant side effects that complicate standard therapeutic interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Following a CMV infection, LILRB1 is mainly expressed on terminally differentiated effector (TEMRA) CD8+ T cells and correlates with “memory inflation”0 . LILRB1 inhibits the CD8+ CTL response, and a high affinity, soluble LILRB1 has been used to study the activation mechanisms of various subsets of CTLs . Inhibition of LILRB1 promotes CD8+ T cell effector responses in the ageing immune system .…”
Section: Lilrb1 Expression On Myeloid Cellsmentioning
confidence: 99%